2016
DOI: 10.1089/neu.2015.3948
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Abnormalities in the Corpus Callosum of Female Concussed Athletes

Abstract: Concussion is an injury affecting millions of individuals annually that can be associated with long-term sequelae. Recent studies have reported long-term abnormalities in the white matter (WM) tracts of male athletes. The corpus callosum (CC) and corticospinal tract (CST) have been shown to be particularly vulnerable to concussion, which may be related to abnormal interhemispheric functional connectivity and motor impairments. These anatomical pathways, however, have not been investigated in female athletes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 46 publications
6
46
1
1
Order By: Relevance
“…As hypothesised, the wearing of the device was effective to prevent diffusion changes after a full season of repetitive head impacts in high school football athletes. Specifically, the CTRL group showed consistent and statistically significant reduction in diffusion coefficients—a change that has been reported frequently in mTBI33–37 and sports-related TBI22 38–44 literature—contrasting with the absence of change in the football players who wore the collar. Combined with the association found between the decrease of diffusivity in the CTRL group and their impact burden, our study has generated initial evidence for a potential protective effect of the collar device.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…As hypothesised, the wearing of the device was effective to prevent diffusion changes after a full season of repetitive head impacts in high school football athletes. Specifically, the CTRL group showed consistent and statistically significant reduction in diffusion coefficients—a change that has been reported frequently in mTBI33–37 and sports-related TBI22 38–44 literature—contrasting with the absence of change in the football players who wore the collar. Combined with the association found between the decrease of diffusivity in the CTRL group and their impact burden, our study has generated initial evidence for a potential protective effect of the collar device.…”
Section: Discussionmentioning
confidence: 55%
“…38–44 WM integrity changes based on DTI have been correlated with postconcussive symptoms and cumulative risk-weighted exposure 40. Prior analyses of DTI in mTBI and sports-related TBI have shown changes of varying severity and direction, including abnormally lower FA and/or higher diffusivity (MD, AD, RD) in patients, concussed athletes, athletes with a history of concussion,25 27 43 46 or decreased FA and/or increased diffusivity measures in athletes when tested for preseason to postseason changes 39…”
Section: Discussionmentioning
confidence: 99%
“…While many of these findings were sex‐dependent and are discussed further in the next section, DTI metrics revealed a significant effect of injury in the contralateral CC with RmTBI rats having significantly lower AD and ADC than shams regardless of sex. Reduced ADC has been observed in the CC of adolescents with mTBI,48 and in university students including concussed male49 and female50 athletes. In the latter study, and consistent with our results here, concussed athletes also had reduced AD in the CC.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have found reduced white matter integrity in the corpus callosum (60, 61), which has also been associated with functional outcome using The Functional Independence Measure and Glasgow Outcome Scale, although in severe TBI (62). Importantly, we did not include DTI-based indices of white matter microstructure in the present analysis, and the relationship between DTI-based measures and white matter volume is complex (63).…”
Section: Discussionmentioning
confidence: 99%